Media system and legal bases of mass media of Germany (Journal of Philosophy Culture and Political Science, 2015)
There is considered mass media of Germany which have the media features,including the sovereignty of federal lands in the field of the press andTV and radio broadcasting or parallel existence of public and private massmedia that is not characteristic for all western countries. Concerning freedomof press and a freedom of speech at Germany has also good positions incomparison with other countries. The pluralism of opinions and pluralism ofinformation is provided at rather high level. The press is not in hands of thegovernments or parties, it is in hands of representatives of society.In Germany representatives of mass media possess big, than someone,rights to collect and distribute information. These rights are a consequenceof a special role of media space in formation of public opinion and serviceto public interests. In Germany the most important element of a freedomof speech and the press is also the pluralism of publications.
Keywords: mass media of Germany; freedom of speech and press; sources of information; press; radio; television; Internet.